MENGAPRESIASI NOVEL SEBAGAI MEDIA DAKWAH BIL-QALAM - Indrawati Indrawati (Wardah, 2013)
The novel as a form of modern literary works created with various objectives . Some of the novelist creates his work with the aim of carrying out propaganda through his ability to write sentences that aesthetic . Aesthetics is in the literature is not only limited to the beauty of the sentence but also in packaging aesthetic elements that build the overall structure of literary works , including a beautiful message in the pack .Thus , the novel as a literary work can take part in efforts to improve the quality of human life because the novel than as a work of imaginative , creative , as well as intellectual work . In it can be found new insights in the form of religious values ( religion ) , intelligentsia ( science ) and a variety of life experiences that can provide insight and breadth of outlook in life is complex . When “Dakwah” is widely interpreted as an effort to encourage people to a better life then at that moment can take on the role of literature